Robust Phenotypic Activation of Eosinophils during Experimental Toxocara canis Infection - Rodolpho, Joice Margareth de Almeida; Camillo, Luciana; Araújo, Márcio Sobreira Silva; Speziali, Elaine; Coelho-dos-Reis, Jordana Grazziela; Correia, Ricardo de Oliveira; Neris, Débora Meira; Martins-Filho, Olindo Assis; Teixeira-Carvalho, Andréa; Anibal, Fernanda de Freitas (Frontiers in Immunology, 2018)
Eosinophils are multifunctional cells that have cytotoxic proinflammatory activities and stimulate CD4+ T-cells in experimental models of allergy and parasitic infections. Eosinophils, when exposed to antigens, are activated, expressing the CD38/CD69 molecules and exhibited increased expression of Major Histocompatibility Complex (MHC-II), CD80 and CD86, suggesting they play a role upon T. canis antigen stimulation. In the present study, we evaluated the profile of eosinophils using conventional and image flow cytometry upon experimental Toxocara canis infection. T. canis antigens induced a robust activation on this subset, contributing to the immune responses elicited in the experimental model for T. canis-associated Visceral Larva Migrans Syndrome (VLMS). Data analysis demonstrated that, during murine T. canis infection, eosinophils from peripheral blood, spleen and bone marrow presented up-regulated expression of CD69/MHC-II/CD80/CD86. As opposed to splenic and bone marrow eosinophils, circulating eosinophils had increased expression of activation markers upon T. canis infection. The enhanced connectivity between eosinophils and T-cells in T. canis-infected mice in all three compartments (peripheral blood, spleen and bone marrow) also supports the hypothesis that eosinophils may adopt a role during T. canis infection. Moreover, in vitro T. canis-antigen stimulation resulted in activation and up-regulation of co-stimulatory-related molecules by bone marrow-derived eosinophils. Our findings are evidence of activation and up-regulation of important activation and co-stimulatory-related molecules in eosinophils and suggest a reshape of activation hierarchy towards eosinophils during experimental T. canis infection.